2021
DOI: 10.1108/sbm-03-2021-0024
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of UEFA Financial Fair Play: evidence from England and France, 2008–2018

Abstract: PurposeThis paper analyses the effectiveness of UEFA's Financial Fair Play (FFP) under the break-even requirement.Design/methodology/approachData was collected from English and French football clubs competing in the English Premier League (EPL) and in Ligue 1 (L1) for the financial years 2008–2018. Our sample includes 395 club-year observations. Relevant statistical tests have been conducted with the aim of analysing the effects of pre (2008–2012) and post (2012–2018) FFP enforcement under both profitability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 50 publications
1
21
0
1
Order By: Relevance
“…On the other hand, such positive outcomes were not found for French, Spanish or Italian clubs (Ahtiainen & Jarva, 2022;Ghio et al, 2019). Francois et al (2021) supported these outcomes by showing the increased profitability of English football clubs compared to French clubs. However, this pattern only applies to entities that are not participating in UEFA internation competition.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 88%
“…On the other hand, such positive outcomes were not found for French, Spanish or Italian clubs (Ahtiainen & Jarva, 2022;Ghio et al, 2019). Francois et al (2021) supported these outcomes by showing the increased profitability of English football clubs compared to French clubs. However, this pattern only applies to entities that are not participating in UEFA internation competition.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 88%
“…UEFA Financial Fair Play was introduced to European football in 2010 because of persistent losses amongst Europe's elite clubs (Francois et al, 2022). Specifically, the purpose of Financial Fair Play is to prevent clubs that qualify for UEFA competitions from spending more than they earn and, consequently, to improve the financial health of European football (García-del-Barrio and Rossi, 2020).…”
Section: Women On Boards and Organisational Performancementioning
confidence: 99%
“…Plumley et al (2019) provided a more refined view of a decline in competitive balance for leagues in Spain, Germany and France but not for England and Italy. In their cross-league comparison, Francois et al (2021) found that player expenditures, the key reason for financial unsustainability, have significantly decreased in the English Premier League since the introduction of the FFP. In terms of the positive impact on the profitability of clubs, Ahtiainen and Jarva (2022) found that the effect has been "modest, at best", calling upon UEFA to enforce the breakeven requirement more fiercely and reassess the efficacy of the Financial Fair Play regulations.…”
Section: The Unsustainability Of the Football Businessmentioning
confidence: 99%